ANALISIS KUALITAS PELAYANAN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH UNDATA PALU PROVINSI SULAWESI TENGAH - Hadijah, Hadijah (Katalogis, 2016)
This research is a descriptive qualitative study, in which descriptive qualitative research is used to depict or describe a situation is on the level of Quality of Hospital Inpatient Services In Undata. Judging from the number of visits patients, especially inpatients has decreased the number of visits that by 2015 as many as 11 192 visits by an average of 69 people a day visit while in 2014 as many as 14 871 visits with an average of 182 people per day. This study was conducted to determine how the Quality of Inpatient Services at Regional General Hospital Undata. The purpose of this study was to determine the quality of Inpatient Services at Regional General Hospital Undata seen from the aspect of tangible, reliability, responsiveness, assurance and empathy. In conclusion, the study proves that the quality of Inpatient Services at Regional General Hospital Undata turns considered less good, because in general there are still many complaints from patients and the public. The results of this study are expected to be useful in improving the quality of care in hospitals Undata, to suit the patient's expectations and the vision, mission Mission Hospital.